Productivity of Sorghum (Sorghum bicolor) Supplied with Organic Pupils Based on Oil Palm Plantation Waste, Cattle Manure, and Agricultural Simbiotic Microbas - Mudhita, Ida Ketut; Saprudin, Saprudin; Kurniawan, Aan; Wijinindyah, Ayutha; Widodo, Agus Tri (Journal of Tropical Animal Science and Technology, 2025)
This study aims to determine the effect of the addition of Organic Fertilizer (OP) made from oil palm plantation waste and cow dung enriched with Agricultural Symbiotic Microbes (ASM) on Sorghum (Sorghum bicolor) production. This research was conducted in Natai Raya Village, Kumai District, West Kotawaringin Regency, Central Kalimantan. The design used was Randomized Complete Block Design (RCBD) consisting of 4 treatments P0= control (100% NPK fertilizer), P1= NPK fertilizer 100%+OP 50% (100 g/plant), P2= NPK 100%+OP 100% (200 g/plant), P3= NPK 100%+OP 150% (300 g/plant). The number of sorghum per plot was 24 plants, and the number of plots per treatment was 3 plots, with a size of 3x2 m (6 m2). Harvesting age of sorghum was 70 days. Parameters observed: plant growth (plant height and number of tillers), and plant production (fresh weight and dry matter). The results showed that the average height of sorghum plants were:  P0 = 181.14 cm, P1 = 204.35 cm (increased 12.81% compared to PO), P2 = 211.81 cm (increased 16.93%), and P3 = 218.79 cm (increased 20.79%). The number of tillers of sorghum plants were: P0= 10.47 stems, P1= 10.53 stems (increased 0.53%), P2= 10.74 stems (increased 2.52%), and P3= 11.01 stems (increased 5.1%). The fresh weight production of sorghum plants and fruits per plot was P0= 13.4 kg or 22.36 tonnes/ha, P1= 17.1 kg or 28.52 tonnes/ha (27.55% increase), P2= 17.5 kg (30.63% increase) or 29.21 tonnes/ha, and P3= 18.2 kg or 35.75 tonnes/ha (35.75% increase). The dry matter production of sorghum plants and fruits per plot were P0= 4.17 kg or 6.94 tonnes/ha, P1= 5.31 kg or 8.85 tonnes/ha, P2= 5.44 kg or 9.07 tonnes, and P3= 5.66 kg or 9.43 tonnes/ha. The conclusion of this research is that the addition of organic fertilizer as much as 150% or 300 g/plant gives the best results on the growth and production of shorghum plants.   Keywords: Growth, Production, Shorghum, Organic Fertiliser, Oil palm plantation waste and cow feces.